DEVELOPMENT OF ARABIC VOCABULARY FLIPBOOK MEDIA BASED ON THE HEYZINE FLIPBOOK PLATFORM FOR EIGHTH GRADE STUDENTS AT MTsS UMMI LUBUK PAKAM - Ivlatia, Siti Mahrami; Al-Rasyid, Harun (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to develop an instructional medium in the form of an Arabic vocabulary flipbook based on the Heyzine Flipbook platform, focusing on the topic of hobbies, which can be used practically in eighth-grade learning at Madrasah Tsanawiyah UMMI Lubuk Pakam. The method employed in this study is Research and Development (R&D) using the 4D model, which consists of four stages: analysis, design, development, and dissemination. The results of the media expert validation showed a percentage of 80%, categorized as “feasible” for use (valid), while the material expert validation obtained a percentage of 88%, categorized as “feasible” for use (valid). Furthermore, the results of the student response questionnaire in the field trial showed a percentage of 98.2%, categorized as “highly feasible,” while the results of the Arabic language teacher's response questionnaire toward the media obtained a percentage of 84%, categorized as “feasible.”